DESAIN KANTOR DINAS PERINDUSTRIAN DAN PERDAGANGAN - Sari Octavia; Henry Soleman Raubaba; Yosi Valentina Simorangkir (Faculty of Engineering, Musamus University, Merauke, Papua, Indonesia., 2019)
The low quality of infrastructure and facilities is one of the causes of hampered services to the community. Infrastructureand offices that are directly related to trade and commerce, Industry and Trade, bearing in mind that Industry and Trade areone of the economic driving forces in the City of Merauke. Dinas Perindustrian dan Perdagangan Kabupaten Merauke officeBuilding tries to approach tropical architecture in its design. This research is a qualitative research by directly observing inthe field, making image recordings and conducting literature studies. This research is research. This study aims to analyzethe application of building concepts with a tropical architectural approach to its qualitative design by making directobservations in the field, making image recordings and conducting literature studies. . The results showed that the buildingdesign applied a tropical architectural approach to setting the basic coefficient of buildings, building orientation, buildingopenings and s / v ratio of buildings. The application of this type of material on building blankets is not maximal consideringthat there are still many materials that are not sustainable (suistainable) and fabrication materials that are not suitable forapplication in buildings with a tropical climate.